Balakrishnan skew logistic distribution. Issue 2 (17th January 2016) - Asgharzadeh, A.; Esmaeili, L.; Nadarajah, S.
Abstract: Based on Balakrishnan's (2002 ) novel idea, a new skew logistic distribution is proposed. It contains Azzalini's skew logistic and standard logistic distributions as particular cases. Several mathematical properties of the proposed distribution (including characteristic function, cumulative distribution function, stochastic orderings, and simulation schemes) are derived. A real-data application is used to illustrate practical usefulness.